Analisis faktor-faktor yang berhubungan dengan kepemilikan jamban pada daerah pesisir kecamatan Koba kabupaten Bangka Tengah provinsi kepulauan Bangka Belitung - Ari Liendy Rachmawati; Ani Margawati; Budi Laksono (Berita Kedokteran Masyarakat (BKM), 2019)
Cadre support and Latrine ownership for coastal residents  in Koba Bangka BelitungPurpose: The behavior of coastal communities who are less accustomed to defecation using latrines has an influence on public health as a whole, especially in diseases related to environmental health. Most of the coastal communities are people with jobs as fishermen who have different characteristics from other communities around them. Problems that often arise in coastal areas are the low level of community welfare and low quality of the environment and sanitation, which has an impact on the ownership of latrines. The purpose of this study was to examine variables associated with healthy latrine ownership in a coastal communities. Method: A survey of 200 families in the coastal villages of Kurau and Kurau Barat of Koba, Central Bangka District. Results: Level of education, knowledge, water availability, support of village administrators were associated with healthy latrine ownership. Families with support from voluntary health worker showed three and a half times more likely to have a toilet at home (OR 3.54, 95% CI 1.44 - 8.69). Conclusion: This study suggests villagers' knowledge of hygiene and sanitation conveyed from the voluntary health workers have a positive impact on the community's response to latrines. Scaling up the voluntary primary health care workers role is important in introducing latrine to villagers.